Clinical and pathologic characteristics of testicular germ cell tumors - Potapov, Serhii M.; Horhol, Nataliia I.; Halata, Daria I.; Pliten, Oksana M. (Journal of Education, Health and Sport, 2019)
The performed analyses of incidence rate of testicular germ cell tumors and clinical and pathologic analysis, based on the examination of pathologists’ reports and medical case histories of the patients of Kharkiv regional clinical center of urology and nephrology named after Shapovalov V.I., for the period covering years 1998-2017, revealed: unfavorable increasing tendency in testicular GCT incidences, the most typical age of patients with mentioned pathology, and average duration of the disease by the time the patient visited the doctor; determined the possible risk factors of testicular GCT development, as well as the morphological traits in accordance with WНO updated classification.